Neutron activation analysis and assessment of trace elements in fingernail from residents of Tokyo, Japan - Wee, B.S.; Ebihara, M. (Penerbit Universiti Kebangsaan Malaysia, 2017)
We report herewith the study of fingernail clippings obtained from the residents of Tokyo, Japan. A total of 18 participants with no health problems and occupational exposure to metals were recruited to provide fingernails samples for this study. Through the use of instrumental neutron activation analysis (INAA), 18 elements (Ag, Al, As, Ca, Cl, Co, Cu, Fe, Hg, K, Mg, Mn, Na, S, Sb, Se, V, and Zn) were determined. The results showed that the toxic elements in the fingernails are in the lower range when compared to literature values. There were no chronic exposures to toxic elements such as As and Hg found. The level of Hg found is lower than that reported 20 years ago, possibly due to the strict regulation control in Japan on the release of Hg to the environment. The elements Se and Zn are found to be rather uniformly distributed among participants and are in agreement with results from other countries. There were no significant differences in elemental concentrations due to genders and smoking habits. The overall data from this study showed similar concentrations to those of healthy participants from other countries. Thus, the current data could represent the background level of elemental concentrations in fingernails of residents in Tokyo, which could serve as reference values for future study.